2023
DOI: 10.1093/plphys/kiad228
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-regulated expansins: Expression, localization, and cell wall biomechanics in Arabidopsis root growth

Abstract: Expansins facilitate cell expansion by mediating pH-dependent cell wall (CW) loosening. However, the role of expansins in controlling CW biomechanical properties in specific tissues and organs remains elusive. We monitored hormonal responsiveness and spatial specificity of expression and localization of expansins predicted to be the direct targets of cytokinin signaling in Arabidopsis (Arabidopsis thaliana). We found EXPANSIN1 (EXPA1) homogenously distributed throughout the CW of columella/lateral root cap, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 105 publications
(177 reference statements)
0
14
0
Order By: Relevance
“…Chickpea seeds, for instance, express auxin signaling genes in preparation for germination (Kudapa et al., 2018). In the embryonic axes of developing seeds, auxin signaling has been shown to loosen cell walls by activating expansins and xyloglucan endotransglycosylases/hydrolases (XTHs), thereby enabling the cells to expand without automatically losing their integrity (Gimeno‐Gilles et al., 2009; Samalova et al., 2023; Wang & Ruan, 2013). As a result of cell wall expansion, the cell wall can become more vulnerable to the activity of cell wall modification enzymes like pectin methylesterases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chickpea seeds, for instance, express auxin signaling genes in preparation for germination (Kudapa et al., 2018). In the embryonic axes of developing seeds, auxin signaling has been shown to loosen cell walls by activating expansins and xyloglucan endotransglycosylases/hydrolases (XTHs), thereby enabling the cells to expand without automatically losing their integrity (Gimeno‐Gilles et al., 2009; Samalova et al., 2023; Wang & Ruan, 2013). As a result of cell wall expansion, the cell wall can become more vulnerable to the activity of cell wall modification enzymes like pectin methylesterases.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of cell wall expansion, the cell wall can become more vulnerable to the activity of cell wall modification enzymes like pectin methylesterases. One study showed that the overexpression of expansin enzymes was able to increase the rate of pectin demethylesterification in Arabidopsis root cells within 3 h, leading to stiffer cell walls within 6 h (Samalova et al., 2023). Changes in cell wall integrity could then lead to changes in cooking time (Chen et al., 2022; Chigwedere et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, at higher N concentrations, H. seropedicae promoted other benefits to the plant, such as shoot length growth, without gain of dry mass ( Figure 9 ). EXPA1 was also up-regulated in INN+ vs CTN+, suggesting changes in the chemical composition of the cell wall that could be possibly modulating root development in response to inoculation under N+, as observed in the overexpression of EXPA1 in Arabidopsis mutant seedlings ( Samalova et al., 2023 ). Thus, our molecular and phenotypic results suggested that under conditions of high N availability, and in the presence of H. seropedicae , there is growth promotion in maize plants, without gain of dry mass.…”
Section: Discussionmentioning
confidence: 89%
“…Expansin proteins are known for their multifaceted roles in plant growth, especially cell walls. Overexpression of EXPA1 was accompanied by changes in the chemical composition of the cell wall leading to changes in root development in Arabidopsis seedlings ( Samalova et al., 2023 ), suggesting that EXPA , together with several genes encoding enzymes involved in cell wall remodeling, may be part of the regulatory network involved in elongation/cell expansion, regulated by GA.…”
Section: Resultsmentioning
confidence: 99%
“…The specificity of expression and localisation of several alpha-expansins was studied in Arabidopsis thaliana (Samalova et al 2023).…”
Section: Expansins Induce Cell Wall Remodellingmentioning
confidence: 99%